2001
DOI: 10.1046/j.1365-2265.2001.01386.x
|View full text |Cite
|
Sign up to set email alerts
|

Currently used growth‐promoting treatment of children results in normal bone mass and density. A prospective trial of discontinuing growth hormone treatment in adolescents

Abstract: After discontinuation of GH therapy in adolescents at or near final height, there was a continued increase in BMC and BMD both for adolescents with growth hormone deficiency and for those classified as growth hormone sufficient. These groups did not differ from controls at baseline or after 2 years. In the growth hormone deficiency group, biochemical markers for bone formation decreased to levels below those in the growth hormone sufficient and healthy control groups. Although the number of patients and contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 43 publications
4
32
0
1
Order By: Relevance
“…Hypothetically, our findings could be caused by frequent physical activity during adolescence leading to a good peak bone mass despite diminishing secretion of growth hormone. Decreased bone turnover has previously been demonstrated in patients with GHD in some (36,37) but not all (38) studies. Neither this study nor the study of Brennan et al found a correlation between growth hormone and markers of bone turnover (9).…”
Section: Discussionmentioning
confidence: 89%
“…Hypothetically, our findings could be caused by frequent physical activity during adolescence leading to a good peak bone mass despite diminishing secretion of growth hormone. Decreased bone turnover has previously been demonstrated in patients with GHD in some (36,37) but not all (38) studies. Neither this study nor the study of Brennan et al found a correlation between growth hormone and markers of bone turnover (9).…”
Section: Discussionmentioning
confidence: 89%
“…In vivo, GH administration increases biochemical markers of bone turnover in normal subjects [36], adults with GHD [37]and children with GHD [38]. Furthermore, children with GHD demonstrate reductions in markers of bone turnover after discontinuation of GH at completion of linear growth [39]. …”
Section: Skeletal Health In Adults With Ghd and The Impact Of Gh Replmentioning
confidence: 99%
“…These results suggest that in young adults with GHD, GH replacement may be needed to support adequate bone mass accumulation in order to maintain bone mass in adult life (21)(22)(23). Furthermore, it seems likely that adolescents with severe GHD may not have achieved their peak bone mass at adult height, when GH treatment is often discontinued, and that GH may play an important role in the acquisition and maintenance of bone mass during this particular period of bone consolidation (3,(24)(25)(26). In addition to reduced BMD, some adults with childhood-onset GHD also have lower lean body mass, diminished quality of life (QoL), abnormal lipids, and impaired cardiac function compared with older adults with adult-onset GHD (27,28).…”
Section: Introductionmentioning
confidence: 99%